Relationship of the nursing practice environment with the quality of care and patients’ safety in primary health care - Pedro Lucas; Élvio Jesus; Sofia Almeida; Beatriz Araújo (BMC Nursing, 2023)
Abstract Background Nursing practice environment has impact on the quality of nursing care and on patients’ and nurses’ outcomes, namely better performances of these healthcare workers. Improving the nursing practice environment is a low-cost organizational strategy to achieve better patients’ outcomes and retain qualified nurses, thus improving nursing care of units, healthcare organizations and healthcare system. This study aims to analyse the relationship between nursing practice environment and the nurses` perception of quality of care, patient safety, and safety culture in Primary Health Care in Portugal. Methods We conducted a descriptive, analytical, and cross-sectional study using data from RN4CAST Portugal. The sample was composed of 1059 nurses from 55 Health Center Groups of the mainland Portugal, 15 Health Centers of the Autonomous Region of Madeira and 6 Health Centers of the Autonomous Region of the Azores. Multivariate analysis and correlation analysis methods were used for data processing. Results Nurses consider that, in the Portuguese Primary Health Care, there is a mixed and unfavourable nursing practice environment, with a perception of a good quality of care, and both acceptable patients’ safety and safety culture. The Collegial Nurse-Physician Relations and Nursing Foundations for Quality of Care dimensions to have the best ratings. The perception of Primary Health Care nurses on the dimension Nurse Participation in Organization Affairs was the one that showed the lowest score, followed by Staffing and Resource Adequacy and Nurse Manager Ability, Leadership, and Support of Nurses. Based on perception of nurses, the relationship between the nursing practice environment and the safety culture is higher, followed by the quality of care and patients’ safety. Conclusions The perception of Primary Health Care nurses is that there is an unfavourable and mixed nursing practice environment, with good quality of care, and acceptable patient safety and safety culture. The quality of the nursing practice environments is associated to better quality and safety of care. Thus, improving the nursing practice environments in healthcare organizations is a low-cost organizational strategy to achieve greater patients and nurses’ outcomes, improving the quality of nursing care to patients in the Primary Health Care units.